(3ScQOGf GdSdWGfs - (3GHf CHj MLdI , CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, TgGH GdOjf CHh GdYHGS,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GfWb GdWjQ HMceJg hHYO adeG cGfJ GdSHYI ef CTQa GdGYOGO hSejJg ScQOGf GdSdWGf s
(3BNQgG (B:s
(3BNQ eG hLO efg dGRGd eMVQ GdMHGH hHjVg JUaQ efgi GdYOh GdGRQb eG GMeQ Tab GdGUjd hOH ShGO YGQVg GdGSeQ HNOg GdG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B994s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs